On Probability Distribution of Preference Among Rewards with Their Benefit Function - Nuri Eltabit Mohamed Almadni (Journal of Libyan Academy Bani Walid, 2025)
assigning a probability function for any reward that a statistician receive is quite challenge. Typically, only he can specify within a certain class of possible distributions, a probability distribution according to his reward will be selected So in this paper we shall specify an appropriate σ-filed F of subset of R (real numbers) and we will consider only probabilities of sets of reward that belongs to F As well as we identify and study the so-called Benefit function of the reward with its property.